Biological relevance of oxidative debris present in as-prepared graphene oxide1. Issue 73 (9th August 2015) - Pattammattel, Ajith; Williams, Christina L.; Pande, Paritosh; Tsui, William G.; Basu, Ashis K.; Kumar, Challa Vijaya
<x xml:space="preserve">Abstract</x> The influence of oxidative debris (OD) present in as-prepared graphene oxide (GO) suspensions on proteins and its toxicity to human embryonic kidney cells (HEK-293T) are reported here.